Interação aditiva, sinérgica ou antagônica de herbicidas aplicados na cultura do milho - Pawelkiewicz, Renan (2018)
The objective of this work was to evaluate the additive, synergic and / or antagonistic effect generated by the application of herbicides applied in isolation or in association with maize crop. The experiment was carried out in a randomized block with 18 treatments and four replicates. The sown corn hybrid was the Agroeste AS 1551 Pro 2 and was submitted to treatments at the V4 development stage. The treatments were applied in isolates or associated, being: nicosulfuron, tembotrione, mesotrione, glyphosate and 2,4-D, besides two witnesses, one weed and another infested. The analyzed variables were phytotoxicity, papuan control and crop yield components. It was observed that the herbicides nicosulfuron, tembotrione and glyphosate when applied in an associated way generated low phytotoxicity and good control of the papua under the conditions in which the experiment was conducted. The herbicides that were selective from 07 to 28 days and effective in controlling the papua at 07 and 14 DAT reflect in an excellent final yield of corn grains. 2,4-D applied in syrup mixtures with other herbicides produced high phytotoxicity on maize observed at 07 to 28 DAT, resulting in loss of grain yield.